A three-dimensional finite element model of a 6-year-old child for simulating brain response from physical reconstructions of head impacts. (June 2019) - Koncan, David; Gilchrist, Michael; Vassilyadi, Michael; Hoshizaki, Thomas Blaine
Despite young children being a high-risk population for sustaining concussive injuries in sport, few studies have investigated head impact biomechanics from sporting impacts using physical models and finite element models of the brain. Physical reconstructions are often used in concussive research, using the recorded kinematics to load finite element models of the brain to obtain better information of real-life head injuries. For children, scaling adult models is a common method used to study the youth population. However, this method does not capture age-dependent material properties or the unique geometry of the developing brain. To address these deficiencies, a novel three-dimensional finite element model of a 6-year-old child was developed and compared to a scaled adult model, for use with physical reconstructions. With the lack of intracranial validation data for the youth population, adult cadaveric data for brain motion was used for comparison. The new brain model showed unique responses in motion and strain compared to the scaled adult model. Using the normalized integral square error method, the new model was classified to have 'fair' to 'excellent' biofidelity. The new model is proposed as more appropriate for conducting concussion and brain injury research in young children near 6 years of age.